PENGARUH ARUS KAS OPERASI,ARUS KAS INVESTASI,ARUS KAS PENDANAAN TERHADAP RETURN SAHAM PADA PT GUDANG GARAM TBK. PERIODE 2012-2021 - Indri Kharisma; Albertus Lasmaroha (JURNAL KONSISTEN, 2024)
Purpose This research aims to determine: The effect of operating cash flow, investment cash flow and funding cash flow on share Returns at PT Gudang Garam Tbk for the 2012-2021 period, both partially and simultaneously Methods This research method uses quantitative. The analytical methods used are descriptive statistical analysis, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), linear regression analysis (simple and multiple linear regression analysis), hypothesis testing (t test and f test), and the coefficient of determination test (R2). Findings he research results show that partially Operating cash flow (X1) influences stock returns (Y). Partially, investment cash flow (X2) has no significant effect on stock returns (Y). Partially, funding cash flow (X3) influences stock returns (Y). Simultaneously there is no significant influence between Operating Cash Flow (X1), Investment Cash Flow (X2), and Funding Cash Flow (X3) on Stock Returns (Y) Implication The high or low chances of a stock return can be determined by the cash flow report. The cash flow report determines the amount of share value received by investors from operating, investment and financing activities